The lichens and lichenicolous fungi of National Nature Park «Biloberezhzhya Svyatoslavа» (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
82 species of lichens and 12 species of lichenicolous fungi are protected on the territory of the National Nature Park «Biloberezhzhya Svyatoslavа». The lichen Athallia alnetorum and lichenicolous fungus Pronectria xanthoriae are the first time reported to Ukraine, 12 species are new for Mykolaiv region, 71 species are new for the National Nature Park. Among lichens, 66 species are corticolous and they were found on the bark of Alnus glutinosa, Pinus sylvestris, Populus tremula, Quercus robur, Salix alba. 12 terricolous species cover sand dunes and sandy steppe areas. 4 species were found on artificial stone substrate. Cetraria aculeata, Seirophora lacunosa, Xanthoparmelia camtschadalis are included into the Red Data Book of Ukraine. Chaenotheca trichialis, Parmelina quercina, Usnea hirta, Xanthoparmelia pokornyi from «Red list» of the Mykolaiv region are protected.
Keywords: Kinburn, Komendantske, Kovalivska saga, Orchidne field, conservation.